Comparison of different blood indices and smear finding among dengue cases: a retrospective review - Smriti Pandey; Dhruvendra Pandey (Tropical Journal of Pathology and Microbiology, 2019)
Background: Dengue disease is typically found in tropical and subtropical regions, where environmental and socioeconomic conditions favor the development of vector, the mosquito Aedes aegypti. Due to changing climate, urbanization, poor living conditions and inadequate waste management, vector borne diseases like dengue fever are becoming more common.Aims & Objectives: This study aims to compare different blood indices among the dengue cases.Material & Methods: A retrospective study among dengue positive cases was conducted at one of the tertiary care centre, Bhopal. Blood sample reports of all the cases from July 2014 to December 2015 was retrieved from records. Total sample size of study was 62 dengue positive cases. All the parameters related to blood smear was recorded and analyzed. The study was approved from institutional ethical committee. Data was analysis using appropriate statistical software.Result: This study included 62 dengue positive cases. In first follow up 41 and in second follow up 28 patients’ details was found. Thrombocytopenia was present in 54.8% cases however 30.6% cases had platelet count below 50000. Median MPV, PDW and hematocrit were 10.15, 15.85 and 40.35% respectively. Low MPV (<9 fl) which indicate bone marrow suppression was observed in 8 (12.9%) patients. High PDW (>13 fl) which is a useful marker for platelet activation seen in 62 (100%) patients.Conclusion: Laboratory parameters and their regular follow up are essential elements of dengue management. Complete blood picture with some indices may predict the chances of dengue positivity. Appearance of platelet clumps in peripheral smear could be used as an early indicator for severity of disease.